MEMBANGUN POLA RELASI KELUARGA BERBASIS KESETARAAN DAN KEADILAN GENDER - Siti Rofi'ah (UIN K.H. Abdurrahman Wahid Pekalongan, 2015)
This study departs from the reality of patriarchal family relationship patterns that distinguish between the role of men (husbands) and women (wives) in the household, where the husband is the head of the family (public) and the wife is a housewife (domestic). Different patterns of family relationships, resulting in injustice and gender in equality. That condition would require the construction pattern of relationships base dongenderequality, to realize a gender partnership to wards a harmonious family. Construction pattern of gender relations gender equality, realized if there is cooperation and division of roles equal and fair between husband and wife, which refers to the planning and implementation of resource management family, so family members have roles in various activities (domestic, public, and social).Kajian ini berangkat dari realitas pola relasi keluarga patriarkhis yang mendikhotomikan peran antara laki-laki (suami) dan perempuan (isteri) dalam rumah tangga, dimana suami adalah kepala keluarga (public) dan isteri adalah ibu rumah tangga (domestik). Pola relasi keluarga yang dikhotomis, mengakibatkan ketidakadilan dan ketidaksetaraan gender. Kondisi tersebut tentunya memerlukan konstruksi pola relasi yang berbasis pada keadilan dan kesetaraan gender, sehingga terwujud kemitraan gender menuju keluarga yang harmonis. Konstruksi pola relasi gender yang berkeadilan dan berkesetaraan gender, terwujud jika ada kerjasama dan pembagian peran yang setara dan adil antara suami dan isteri, yang merujuk pada perencanaan dan pelaksanaan manajemen sumberdaya keluarga, sehingga anggota keluarga mempunyai pembagian peran dalam berbagai aktivitas (domestik, publik, dan kemasyarakatan).